Applying Ant Colony Optimization to the Problem of Cell Planning in Mobile Telephone System Radio Network - Viera Carcache, Osmar; Vinces Llaguno, Leonardo; Guerrero Goyes, Kenya; Marcillo Vera, Fabricio (Enfoque UTE, 2017)
This paper presents a computational proposal for the solution of the Cell Planning Problem. The importance of this problem in the area of Telecommunications imposes it as a reference in the search for new methods of optimization. Due to the complexity of the problem, this work uses a discrete relaxation and proposes a mathematical model for the application of the Meta-heuristic Ant Colony Optimization (ACO). For the analysis of the results, 5 instances of the problem of different sizes were selected and the Ants System (AS) algorithm was applied. The results show that the proposal efficiently explores the search space, finding the optimal solution for each instance with a relatively low computational cost. These results are compared with 3 evolutionary alternatives of international reference that have been applied to the same study instances, showing a significant improvement by our proposal.